Novel approaches to access and treatment of cavernous sinus dural arteriovenous fistula (CS-DAVF): case series and review of the literature. (24th November 2016) - Wenderoth, Jason
Abstract : Caroticocavernous fistula or cavernous sinus dural arteriovenous fistula (CS-DAVF) has presented various treatment challenges over many years. This paper outlines these challenges in a review of the literature, and attempts to address them by analyzing the anatomical and hemodynamic characteristics of 32 consecutive patients with CS-DAVF treated between 2007 and 2016, in doing so proposing novel strategies for safe access and treatment of CS-DAVF.